The Uses of Cloud Storage: A Study on Accounting Student of Economic and Business Faculty at Brawijaya University - Ramadhan, Rifqi Dhia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The aim of this study is to examine the effect of Perceived Usefulness, and Perceived Ease of Use from Technology Acceptance Model (TAM), Social Influence and Facilitating Condition Â Â moderated by gender and age from Unified Theory of Acceptance and Use of Technology (UTAUT) and Personal Innovativeness towards the Behaviour Intention to use and ultimately the actual use of Cloud Storage among the Undergraduate Accounting student at the Faculty of Economic and Business, Brawijaya University. The sample of this research is selected using convenience-sampling method. The total amounts of the usable data are 181. The research data and hypothesis are analyzed using structural equation modelling (SEM) based on partial least squares (PLS). The result shows that. Perceived Usefulness has the most significant influence towards the intention to use among the other variables.Keywords: Cloud Storage, Theory of Acceptance Model, Unified Theory of Acceptance and Use of Technology, Personal Innovativeness.